Quality Improvement to Increase Breastfeeding in Preterm Infants: Systematic Review and Meta-Analysis - Fang, Lingyu; Wu, Lianqiang; Han, Shuping; Chen, Xiaohui; Yu, Zhangbin (Frontiers in Pediatrics, 2021)
Background and Objective: Due to its numerous health benefits, breast milk is recommended for preterm infants. Despite such recommendations, the rates of breastfeeding in preterm infants are lower than that in term infants. Quality improvement (QI) bundles increase breastfeeding in preterm infants, but their replication in neonatal intensive care units has had inconsistent outcomes. Methods: We used the PICO (Population or Problem, Intervention, Comparison, and Outcomes) framework to develop our search strategy, and searched MEDLINE, Embase, and the Cochrane Library from inception through 15 January, 2021. Studies describing any active QI intervention to increase breast milk use in preterm infants were included. The primary outcome measure was the rate of any breastfeeding or exclusive mother’s own milk (MOM) at discharge or during hospitalization. Results: Sixteen studies were eligible for inclusion and showed an acceptable risk of bias, and included 3 interrupted time series, 3 controlled before-and-after trials, and 12 non-controlled before-and-after studies; of these, 3 studies were excluded due to insufficient dichotomous data, 13 were included in the meta-analysis. In the meta-analysis, the rate of any breastfeeding was significantly improved at discharge and during hospitalization after QI (risk ratio [RR] = 1.23, 95% confidence interval [CI]: 1.14–1.32, P < 0.00001 and RR = 1.89, 95%CI: 1.09–3.29, P = 0.02, respectively). The rate of exclusive MOM after QI was also significantly increased at discharge (RR = 1.51, 95%CI: 1.04–2.18, P = 0.03), but not during hospitalization (RR = 1.53, 95%CI: 0.78–2.98, P = 0.22). However, after sensitivity analysis, the comprehensive results still suggested that QI could significantly improve the rate of exclusive MOM (RR = 1.21, 95%CI: 1.08–1.35, P = 0.001). Funnel plots and Egger’s test indicated publication bias in the rate of any BF at discharge. We corrected publication bias by trim and fill analysis, and corrected RR to 1.272, 95%CI: (1.175, 1.369), which was consistent with the results of the initial model. Conclusions: A QI bundle appears to be effective for promoting breast milk use in preterm infants at discharge or during hospitalization.